Gradual Advance of Sleep-Wake Schedules Before an Eastward Flight and Phase Adjustment After Flight in Elite Cross-Country Mountain Bikers: Effects on Sleep and Performance. Issue 4 (22nd April 2023) - Garbellotto, Lucas; Petit, Elisabeth; Brunet, Emmanuel; Guirronnet, Sandrine; Clolus, Yvan; Gillet, Valérie; Bourdin, Hubert; Mougin, Fabienne
Abstract: Garbellotto, L, Petit, E, Brunet, E, Guirronnet, S, Clolus, Y, Gillet, V, Bourdin, H, and Mougin, F. Gradual advance of sleep-wake schedules before an eastward flight and phase adjustment after flight in elite cross-country mountain bikers: effects on sleep and performance. J Strength Cond Res 37(4): 872–880, 2023—Strategies, for alleviating jet lag, specifically targeted to competitive athletes have never been studied, in ecological conditions. This study aimed to assess the effects of a phase advance before a 7-hour eastward flight followed by a strategy of resynchronization at destination on sleep and physical performance in professional mountain bikers. Six athletes participated in this study divided into 4 periods: (i) baseline (usual sleep-wake rhythm); (ii) phase advance (advance sleep-wake schedules of 3 hours for 6 days); (iii) travel (flight: Paris-Tokyo); and (iv) phase adjustment (resynchronization of sleep-wake schedules). Melatonin pills and light therapy were administrated during the phase advance and phase adjustment. Sleep was recorded by polysomnography and actigraphy, core body temperature (CBT) rhythm was assessed by ingestible capsules, and physical performances were tested by the Wingate and 5-minute maximal exercise tests. Results showed that bedtime was advanced by 2.9 hours at the end of the phase advance ( p ≤ 0.01) with a batyphase of CBT advanced by 2.5 hours ( p = 0.07). Bedtime was similar at destination compared with baseline. Total sleep time and sleep composition were unchanged at the end of the phase advance or at destination, compared with baseline. Physical performances were maintained after phase advance and at destination. The phase advance enabled to preshift part of the time zones without disturbing sleep and physical performances and contributed to preserving them once at destination. A phase advance before eastward travel represents an effective strategy to counter harmful effects of jet lag.